menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
If k(x) = 5x – 6, which expression is equivalent to (k + k)(4)? 05(4 + 4) - 6 O 5(5(4)-6) - 6 O 54 – 6 + 54 - 6 o 5(4) - 6 + 5(4) - 6
asked
May 27, 2020
42.4k
views
4
votes
If k(x) = 5x – 6, which expression is equivalent to (k + k)(4)?
05(4 + 4) - 6
O 5(5(4)-6) - 6
O 54 – 6 + 54 - 6
o 5(4) - 6 + 5(4) - 6
Mathematics
middle-school
Vortexwolf
asked
by
Vortexwolf
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
k(x)=5x-6
k(4)=5(4)-6
(k+k)(4)=k(4)+k(4)
=5(4)-6+5(4)-6
I think.
Aadil Mehraj
answered
Jun 3, 2020
by
Aadil Mehraj
5.1k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
Solve for h 3h=7(2/7-3/7h)-10
1/7 + 3/14 equivalent fractions
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org